Introduction Theory and Practice Court Procedural Law Constitution - Saragih, Sepriandison; Gultom, Sarles; Moonti, Roy Marthen (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Laws that develop in society sued the Court for follow development law these, including procedural law. Development procedural law of the Constitutional Court in practice need ijtihad from the Constitutional Court in skeleton find law new to use enforce supremacy constitution, democracy, justice and rights constitutional inhabitant country. Writing this use method approach juridical normative: that is the approach used for study or analyze secondary data in the form of materials primary law and materials law secondary Terms general procedural law arrange about provisions that are general, i.e provision about trial, conditions application, and regarding verdict. Provision in Thing trial in the Constitutional Court, for example, the Court examines, hears, and cut off in hearing plenary attended by all judges consisting of over 9 (nine) people, only in " outside " state normal”, then hearing plenary the attended at least 7 (seven) Constitutional Justices. State outside normal that meant is die world or disturbed physical / soul so that no capable doing the obligation as Judge. Conclusion from article this is The Constitutional Court's procedural law is intended as applicable procedural law by general in things that become the authority of the Constitutional Court as well as applicable procedural law by special for every authority meant. The existence of the Court with the authority possessed bring up needs existence law new, that is procedural law, and develop it in skeleton enforce law in Indonesia.